1989
DOI: 10.1139/v89-274
|View full text |Cite
|
Sign up to set email alerts
|

Ligand substitution reactions of pentacyanoferrate(II) complexes with N-heterocyclic cations in aqueous solution

Abstract: This paper is dedicated to Professor Ronald J. Gillespie on the occasion of his 65th birthday DONAL HUGH MACARTNEY and LAUREN JEAN WARRACK. Can. J. Chem. 67, 1774 (1989). Kinetic and spectroscopic studies have been carried out in aqueous solution on the formation (from F~( c N )~O H~' -) and dissociation of pentacyanoferrate(I1) complexes containing 1-(4-pyridy1)pyridinium and the neutral, protonated, and N-methylated forms of 4,4'-bipyridine (BPY), 1,2-bis(4-pyridy1)ethane (BPA), and trans-l,2-bis(4-pyridy1)e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Of particular relevance to our investigations, the complex [Fe II (CN) 5 (MeQ + )] 2- (MeQ + = N -methyl-4,4‘-bipyridinium) was first reported by Toma and Malin,5a but only very limited characterization data were presented at the time (i.e., UV−vis absorption data). Subsequent studies with this particular complex have included 13 C NMR spectroscopy, photochemical ligand loss,5b outer-sphere complexation, cyclic voltammetric data, 5d, formation kinetics, and the effects of inclusion into a cyclodextrin cavity . The outer-sphere complexation properties and formation kinetics of the closely related complex [Fe II (CN) 5 (Mebpe + )] 2- (Mebpe + = N -methyl-4-[ trans -2-(4-pyridyl)ethenyl]pyridinium) have also been investigated. , In the present study, we have prepared a series of complex salts Na 2 [Fe II (CN) 5 L] (where L is MeQ + , Mebpe + , or a related pyridyl pyridinium ligand) and investigated their electronic and optical properties by using a range of techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular relevance to our investigations, the complex [Fe II (CN) 5 (MeQ + )] 2- (MeQ + = N -methyl-4,4‘-bipyridinium) was first reported by Toma and Malin,5a but only very limited characterization data were presented at the time (i.e., UV−vis absorption data). Subsequent studies with this particular complex have included 13 C NMR spectroscopy, photochemical ligand loss,5b outer-sphere complexation, cyclic voltammetric data, 5d, formation kinetics, and the effects of inclusion into a cyclodextrin cavity . The outer-sphere complexation properties and formation kinetics of the closely related complex [Fe II (CN) 5 (Mebpe + )] 2- (Mebpe + = N -methyl-4-[ trans -2-(4-pyridyl)ethenyl]pyridinium) have also been investigated. , In the present study, we have prepared a series of complex salts Na 2 [Fe II (CN) 5 L] (where L is MeQ + , Mebpe + , or a related pyridyl pyridinium ligand) and investigated their electronic and optical properties by using a range of techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies with this particular complex have included 13 C NMR spectroscopy, photochemical ligand loss,5b outer-sphere complexation, cyclic voltammetric data, 5d, formation kinetics, and the effects of inclusion into a cyclodextrin cavity . The outer-sphere complexation properties and formation kinetics of the closely related complex [Fe II (CN) 5 (Mebpe + )] 2- (Mebpe + = N -methyl-4-[ trans -2-(4-pyridyl)ethenyl]pyridinium) have also been investigated. , In the present study, we have prepared a series of complex salts Na 2 [Fe II (CN) 5 L] (where L is MeQ + , Mebpe + , or a related pyridyl pyridinium ligand) and investigated their electronic and optical properties by using a range of techniques. The results obtained allow us to make detailed comparisons between the new compounds and related complex salts containing {Ru II (NH 3 ) 5 } 2+ electron-donor groups and also to demonstrate a novel chemical approach to switching of molecular NLO responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive series of complexes have been synthesized from with N, O, and S donor ligands. These transfer from the d orbital of iron(II) to * orbitals of the heterocycles [6,7]. It has been demonstrated that the complexation reactions of with a In this article we report the kinetics of formation and dissociation, spectral properties, and equilibrium constants of pentacyanoferrate(II) complexes of 1,3,5-triazine(tri), isoxazole (isox), pyridinecarbonitrile(pyCN), indoline(ind), 1,2-bis(4-pyridyl)etan(bpe), 3-mercapto-1,2,4-triazole(mtr), 2-tiyazoline-2-thiol(tt), picoline(pcl), and pyrazine(pz) in aqueous solution.…”
Section: ϫmentioning
confidence: 99%
“…An extensive series of complexes have been synthesized from with N, O, and S donor ligands. These 3Ϫ Fe(CN) H O 5 2 complexes exhibit well-defined metal to ligand charge-transfer (MLCT) absorption, due to electron transfer from the d orbital of iron(II) to * orbitals of the heterocycles [6,7]. It has been demonstrated that the complexation reactions of with a 3Ϫ Fe(CN) H O 5 2 variety of ligands L and the dissociation reactions of in the presence of excess triazine, follow 3Ϫ Fe(CN) L , 5 a dissociative mechanism.…”
Section: Introductionmentioning
confidence: 99%